Alfabetização científica através do desenvolvimento de pesquisas sobre a biodiversidade regional em uma escola de ensino médio em tempo integral - Brito, Ana Maria Alves de (2020)
Scientific literacy presupposes a critical questioning of knowledge, whether scientific or not. Seeking to stimulate the ability to interpret phenomena while enabling the student to apply knowledge in problem solving and decision making. In this sense, the purpose of the present work was to develop the capacity for critical reading and autonomy, so that students could develop the necessary tools at school, capable of being taken to non-formal teaching spaces, stimulating conscious and reflective interaction in their community. For conducting the research, active methodologies were applied and the development of projects and research that dealt with contents associated with regional biodiversity. This theme was chosen considering the relevance of the subject in the formation of students' cultural identity and the possibility of exploring prior knowledge, to promote scientific literacy, which led to significant learning. The conduct of the research coincided with the period of the Scientific Initiation elective course and lasted for six months. During this period, three phases of the research were carried out: planning, process and products. The planning phase consisted of developing activities that stimulate students' reflection and autonomy on the diversity and classification of living beings. In the process phase, project writing activities, data collection and analysis and work writing were carried out; and, in the product phase, blogs, comics, pamphlets and a fossil workshop were developed by students and applied to all classes in the first year of high school. These actions demonstrated the students' ability to put into practice the concepts visualized in the classroom for their own benefit and that of the community. As a result, scientific literacy was expressed by students when they demonstrated their ability to understand the language of science with criticality and autonomy in the course of conducting research on regional biodiversity. This ability was assessed and measured by comparing the information collected in questionnaires and focus groups, carried out at the beginning and at the end of the research. it was used as parameters of scientific literacy, axes and indicators available in Sasseron (2008). Therefore, the initial objectives of scientific literacy were achieved through the study of regional biodiversity, perceived when comparing the results collected at the beginning of the research with the results collected at the end of the research. The investigative activities applied in this research were recorded in a manual of pedagogical practices, where the experiences can help teachers to teach investigative classes with regional resources, promoting scientific literacy. And from this experience, new scientific literacy activities in high school classrooms can be developed through the use of active, investigative and research methodologies.